The Effect Of Applying Colaborativve Strategic Reading On Students’ Reading Comprehension Achievement - MERLIN Helentina Napitupulu (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2014)
Having an effective way of solving the problems on reading comprehension of narrative text will surely give definite result on students’ reading comprehension achievement. To get the improvement, it is very necessary to apply strategy which is effective so help the students comprehend the reading text. This study was conducted at SMK Smart School Medan. The population of the study is the students of second grade and the sample chosen randomly. They are divided into two groups: the experimental group and control group. Experimental group is the students who are given treatment by using CSR Strategy while the second group, Control group, is the students’ who aren’t given treatment of CSR Strategy. The research design of this study is experimental design. The result of the t-test is that t-observe < t-table (0.239 < 1.984) and p value: 0.812 > 0.05. Therefore the hypothesis is proved to be true that applying Collaborative Strategic Reading in teaching reading comprehension of narrative text is proved to improve effectively the students’ reading comprehension achievement. Key words: reading comprehension, Collaborative Strategic Reading, narrative text